Efficacy of Cognitive-Behavioral Therapy for the Prophylaxis of Migraine in Adults: A Three-Armed Randomized Controlled Trial - Klan, Timo; Gaul, Charly; Liesering-Latta, Eva; Both, Bernhard; Held, Isabella; Hennemann, Severin; Witthöft, Michael (Frontiers in Neurology, 2022)
Background Behavioral approaches are central to the preventive treatment of migraine but empirical evidence regarding efficacy and effectiveness is still sparse. This study aimed to evaluate the efficacy of a newly developed migraine-specific, integrative cognitive-behavioral therapy program (miCBT) combining several approaches (trigger and stress management, coping with fear of attacks, relaxation training) by comparing it with a single behavioral approach (relaxation training, RLX) as an active control group and a waiting-list control group (WLC). Methods In a three-armed open-label randomized controlled trial, 121 adults with migraine were assigned to either miCBT, RLX or WLC. The outpatient group therapy (miCBT or RLX) consisted of seven sessions each 90 min. Participants who completed the WLC were subsequently randomized to one of the two treatment groups. Primary outcomes were headache days, headache-related disability, emotional distress, and self-efficacy. The baseline was compared to post-treatment, and followed by assessments 4- and 12-months post-treatment to compare miCBT and RLX. Results Mixed-model analyses (intention-to-treat sample, 106 participants) showed significantly stronger pre-post improvements in self-efficacy (assessed by the Headache Management Self-Efficacy Scale, HMSE-G-SF) in both treatment groups compared to the WLC (mean difference at post; miCBT: 4.67 [0.55–8.78], p = 0.027; RLX: 4.42 [0.38 to 8.46], p = 0.032), whereas no other significant between-group differences were observed. The follow-up analyses revealed significant within-group improvements from baseline to 12-month follow-up in all four primary outcomes for both treatments. However, between-group effects (miCBT vs. RLX) were not significant at follow-up. Conclusion The miCBT has no better treatment effects compared to RLX in migraine-prophylaxis. Both treatments effectively increase patients' self-efficacy. Trial Registration German Clinical Trials Register (www.drks.de; DRKS-ID: DRKS00011111).